“We call it Bokoa jwa tlhaloganyo”: Setswana parents’ perspective on autism spectrum disorder - Melamu, Neo Jeanett; Tsabedze, Wandile Fundo; Erasmus, Petro; Schlebusch, Liezl (Frontiers in Psychiatry, 2024)
Introduction There is a dearth of knowledge in South Africa about the incidence, prevalence, and effect of autism spectrum disorder (ASD). Consequently, national autism data is outdated, and World Health Organization (WHO) prevalence rates are being used. Methods This study focused on Ngaka Modiri Molema District to explore the cultural perspective of ASD in the Setswana culture from a parental or caregiver perspective, specifically those who attended the World Health Organization Caregiver Skills Training (WHO-CST) on ASD. This qualitative study used a phenomenological design and purposively sampled 6 out of 12 participants who wererecipients of WHO-CST. Semi-structured interviews, audio recordings, and field notes were used to collect data. Results The study found five main themes: understanding autism, indigenous perceptions of ASD, ways of interacting with children living with autism spectrum disorder, creating a friendly environment and symptoms of ASD. Discussion It was concluded that there is a lack of knowledge in Setswana culture about what ASD entails, and there are still some superstitious beliefs regarding ASD, resulting in late diagnoses. ASD studies with larger sample sizes, including medical professionals and policymakers, are recommended.